Mapping of β-lactoglobulin − mucin interactions in an in vitro astringency model: Phase compatibility, adsorption mechanism and thermodynamic analysis. (August 2022) - Ahmad, Mehraj; Ritzoulis, Christos; Bushra, Rani; Meigui, Huang; Zhang, Xinyu; Chen, Jianshe; Song, Junlong; Jin, Yongcan; Xiao, Huining
Abstract: This study investigates the astringency-related interfacial behaviour, mechanistic parameters, and interaction mechanisms of a typical milk protein, β-lactoglobulin (β-LG), with mucin acting as model salivary protein. For a series of β-LG – mucin compositions, the most intense phase separation is observed for a 75:25 w/w mixture of mucin and β-LG at pH 3. QCM-D shows that, at pH 3, β-LG adsorption on a mucinous interface yields a heavily-hydrated viscoelastic layer with increased energy dissipation [Δ D ≤ 9.92 ± 0.01 ( × 10 −6 ], thickness (Δ t = 25.51 ± 0.01 nm), and wet mass values (Δ m = 2623.30 ± 1.27 ng cm −2 ). At pH 7, β-LG (Δ m = 855.86 ± 0.45 ng cm −2 ) forms highly-ordered (more rigid), relatively less dissipative, but thinner interfacial layer, as indicated by the decreased Δ t (7.13 ± 0.01 nm) and Δ D values [≤ 2.52 ± 0.01 ( × 10 −6 )]. Furthermore, Δ D vs. Δ f plots point to the existence of greater conformational and molecular reordering upon progressive coupling of β-LG at pH 3, as compared to pH 7. β-LG exhibits a two-step binding with mucin at pH 3; whilst a single-step (low affinity) mechanism exists at pH 7, as elucidated by fluorimetry. Thermodynamic analysis suggests two macromolecular populations interact spontaneously (Δ G < 0) regardless of pH. Interestingly, Δ S values are substantially greater at pH 3 (≥182.76–292.30 J K −1 M −1 ), in comparison with pH 7 (≤17.07 J K −1 M −1 ); suggesting that entropy-driven flocculation of β-LG and mucin arise from well-defined electrostatic and/or hydrophobic forces. The above results highlight the inherent complexity of pH-induced β-LG – mucin interactions, and the resulting complexity of the physicochemical basis of astringency. Graphical abstract: Image 1 Highlights: At pH 3, co-existence of mucin and β-LG at 3:1 ratio resulted in phase separation. Electrostatic attractions were prevalent in the two-phase aggregates below pH 5. Mass accumulation and conformational rearrangement were pronounced at pH 3. β-LG binds to mucin in a high affinity two-step interaction mechanism at pH 3. Low affinity single-step binding stabilise the two macromolecules at pH 7.